Penerapan Sistem Insentif Tunjangan Kinerja Daerah (TKD) untuk Meningkatkan Kinerja Pegawai di Propinsi Gorontalo - Puluhulawa, Jusdin (Universitas Brawijaya, Indonesia, 2011)
The objective of research is to answer the problems such as: how is the application of incentive system of local performance benefit (TKD). Result of research concludes that the application of incentive system of TKD to improve the performance of employee at Gorontalo Province must be supported by: (1) law umbrella for the certainty of application; (2) the controlled an efficient TKD's budget source and budgeting process; (3) the valid and reliable instrument of assessing employee performance; (4) reward and punishment system; and (5) the efforts to improve employee performance. Research considers qualitative approach to review some phenomena related to performance-based incentive system in the bureaucracy: (a case study on local performance benefit to improve the employee performance at Gorontalo Province) and its solution alternative. Data collection techniques include interview, observation and documentation